2005
DOI: 10.1007/s10447-005-3185-3
|View full text |Cite
|
Sign up to set email alerts
|

Voices in the Wilderness: Counselling Gifted Students in a Swedish Egalitarian Setting

Abstract: An egalitarian setting; that is, a setting established on an ideological and cultural basis, in which individual differences traditionally is a sensitive and often problematic issue, the counseling of gifted individuals present a particular problem. Sweden provides the setting in which the current study was carried out. This qualitative case study focuses on how one highly gifted individual-a 27-year old male-has experienced his school years and university training and how successful counselling for him was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As one respondent puts it, “You can get support if you don’t quite perform, but if you do more, you are expected to tone it down.” The children at the high end of the spectrum may therefore be left to themselves, without adequate recognition of their needs, indeed without even knowing “what’s wrong.” School experiences as well as society’s egalitarianism may have implications for development, adjustment, and view of self up into adulthood. Persson (2005) argued that in Sweden, the common view is that high-functioning cognitive abilities are best hidden and require no special attention. Thus, it seems that the advantages of high abilities are not recognized, while the potentially stressing social disadvantages, such as feeling different, not being accepted, and not fitting in, are left unmanaged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one respondent puts it, “You can get support if you don’t quite perform, but if you do more, you are expected to tone it down.” The children at the high end of the spectrum may therefore be left to themselves, without adequate recognition of their needs, indeed without even knowing “what’s wrong.” School experiences as well as society’s egalitarianism may have implications for development, adjustment, and view of self up into adulthood. Persson (2005) argued that in Sweden, the common view is that high-functioning cognitive abilities are best hidden and require no special attention. Thus, it seems that the advantages of high abilities are not recognized, while the potentially stressing social disadvantages, such as feeling different, not being accepted, and not fitting in, are left unmanaged.…”
Section: Discussionmentioning
confidence: 99%
“…School experiences as well as society's egalitarianism may have implications for development, adjustment, and view of self up into adulthood. Persson (2005) argued that in Sweden, the common view is that high-functioning cognitive abilities are best hidden and require no special attention. Thus, it seems that the advantages of high abilities are not recognized, while the potentially stressing social disadvantages, such as feeling different, not being accepted, and not fitting in, are left unmanaged.…”
Section: Sense Of Coherencementioning
confidence: 99%
“…With qualitative methods, Hébert and Olenchak (2000) examined the mentorship experiences of three students and found that an open-minded, nonjudgmental, strengths-focused mentor could help underachievers regardless of the their age or circumstances. Persson's (2005) qualitative case study in Sweden was focused on "received mentorship" to provide counseling support for gifted individuals in an egalitarian setting that did not emphasize individual differences.…”
Section: Studies Of Approachesmentioning
confidence: 99%
“…Bjorn, Swedish, now in his mid-30s, was also plagued by teachers and school and received no stimulation at all during his school years (a full case study has been done on Bjorn, see Persson, 2005). In fact, it went so far that he decided to "limit his own capacity to think and reason" by sniffing a harmful solvent, which he argued would damage his brain only "a little".…”
Section: Bjorn the Caring Intellectual Persuadermentioning
confidence: 99%